Inactivation of simian immunodeficiency virus by hydrostatic pressure. - Jurkiewicz, E (1995)
The inactivation of the simian immunodeficiency viruses SIVmac251 and SIVagm by pressures of 150 and 250 MPa was determined. The extent of inactivation depended on the time that the virus was subjected to compression as well as the level of the pressure and at 150 Mpa reached 5 log10 dilution units after approximately 10 hr. The inactivations, which were uniformly carried out at room temperature, were independent of the concentration of the virus. Possible applications of pressure inactivation for molecular biological and clinical use are discussed.